2019
DOI: 10.1002/humu.23801
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of new variants at the Low Density Lipoprotein Receptor associated with familial hypercholesterolemia

Abstract: Familial hypercholesterolemia is an autosomal dominant disease of lipid metabolism caused by defects in the genes LDLR, APOB, and PCSK9. The prevalence of heterozygous familial hypercholesterolemia (HeFH) is estimated between 1/200 and 1/250. Early detection of patients with FH allows initiation of treatment, thus reducing the risk of coronary heart disease. In this study, we performed in vitro characterization of new LDLR variants found in our patients. Genetic analysis was performed by Next Generation Sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Simultaneously expressing the variants and wild-type protein in cells to check the diversity of their function hinted at a pathogenesis role. Despite being widely used, several drawbacks exist, particularly the difficulty of normalizing the diversity of their function to their expression (24)(25)(26). CRISPR/Cas9 enables the editing of genomic DNA directly, excluding the impact of the aforementioned issues.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously expressing the variants and wild-type protein in cells to check the diversity of their function hinted at a pathogenesis role. Despite being widely used, several drawbacks exist, particularly the difficulty of normalizing the diversity of their function to their expression (24)(25)(26). CRISPR/Cas9 enables the editing of genomic DNA directly, excluding the impact of the aforementioned issues.…”
Section: Discussionmentioning
confidence: 99%
“…LDLR variants were classified as activity defective or activity negative ("null") according to variant type; nonsense, frameshift and copy number variants were classed as "null" and other variants classed as "defective" unless functional studies have demonstrated otherwise. 12,13 The association between GRS and CAD was investigated using logistic regression analyses that adjusted for the established predictors of increased CAD risk: age, sex, hypertension, type-2 diabetes, smoking status, Lp(a) levels and treatment-adjusted LDL-c. The association between GRS and coronary calcium score was investigated using linear regression adjusting for the same established predictors of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between GRS and clinical and anthropometric characteristics was assessed using linear and logistic regression as appropriate. LDLR variants were classified as activity defective or activity negative (“null”) according to variant type; nonsense, frameshift and copy number variants were classed as “null” and other variants classed as “defective” unless functional studies have demonstrated otherwise . The association between GRS and CAD was investigated using logistic regression analyses that adjusted for the established predictors of increased CAD risk: age, sex, hypertension, type‐2 diabetes, smoking status, Lp(a) levels and treatment‐adjusted LDL‐c.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the uptake and degradation of 125 I‐labelled LDL in cultured skin fibroblasts was measured . A variety of methods is now used, including flow cytometry of transfected Chinese hamster ovary cells using fluorescent‐labelled LDL to determine receptor activity, with immunofluorescence detected by confocal laser scanning microscopy to assess LDL receptor expression and localisation within the cell; and mRNA studies …”
Section: Pathophysiology and Molecular Geneticsmentioning
confidence: 99%
“…12 A variety of methods is now used, including flow cytometry of transfected Chinese hamster ovary cells using fluorescent-labelled LDL to determine receptor activity, with immunofluorescence detected by confocal laser scanning microscopy to assess LDL receptor expression and localisation within the cell; and mRNA studies. [13][14][15][16] The reality of the contemporary investigation of FH has been an explosion in the detection of LDLR variants, many of which are labelled as causative, but functional assays of LDL receptor activity, representing the gold-standard confirmation of pathogenicity, are rarely performed. Generally, the pathogenicity of a new variant is assessed by a number of means, supported by guidelines from the American College of Medical Genetics and Genomics (ACMG).…”
Section: Variants In Ldlrmentioning
confidence: 99%